An Empirical Research on the Economic Impact of War on Citizens and Consumers: The Case of Russian Ukrainian War - Alexandru – Mihaita ICHIM; Teodora Monica FULGA (Communications of International Proceedings, 2024)
This study provides a comparative analysis of the impact of the Ukraine war (February 2022 - December 2023) on consumer behavior in the European Union and South Korea. The research fills a gap in the literature by examining the effects of a military crisis on two economically connected regions sharing borders with the instigating country. Utilizing the Difference-in-Difference (DiD) statistical technique, the study analyzes the evolution of the Consumer Price Index (CPI) for food, non-alcoholic beverages, and energy. The 21st century, despite technological advancements and lessons from history, has not been immune to conflicts, as exemplified by the Russia-Ukraine war. This conflict, occurring on the “old continent” and affecting the EU, one of the world’s largest democratic alliances, highlights the disparities between nations in the modern era. The research aims to elucidate how this war has affected the citizens of the EU and South Korea, two significant global powers, through changes in the CPI. The study is structured into eight sections, including an introduction, literature review, methodology, results and discussions, conclusions, research limits, future research, and bibliography. The findings present a comprehensive view of the war’s impact on the citizens of these regions, contributing significantly to the understanding of the economic repercussions of military conflicts.
Keywords: war; Ukraine; Russia.